Increased Microvessel and Arteriole Density in the Contracted Side of the Relapsed Clubfoot - Novotny, Tomas; Eckhardt, Adam; Knitlova, Jarmila; Doubkova, Martina; Ostadal, Martin; Uhlik, Jiri; Musilkova, Jana (Journal of pediatric orthopedics, 2020)
BACKGROUND: Clubfoot deformity (pes equinovarus) is one of the most common birth defects, and its etiology is still unknown. Initial clubfoot treatment is based on the Ponseti method throughout most of the world. Despite the effectiveness of this therapy, clubfoot may relapse. Recent studies confirm the theory of active fibrotic remodeling processes in the extracellular matrix of the affected tissue. The aim of this study was to clarify whether relapses in clubfoot therapy are associated with altered angiogenesis and to suggest possible regulatory pathways of this pathologic process. METHODS: We compared microvessel density, arteriole density, and concentration of angioproliferative-related proteins found between tissues in the contracted, that is, the medial side (M-side), and noncontracted, that is, the lateral side (L-side) of the relapsed clubfeet. Tissue samples from 10 patients were analyzed. Histopathologic analysis consisted of immunohistochemistry and image analysis. Real-time polymerase chain reaction was used to study mRNA expression. RESULTS: An increase in microvessel and arteriole density was noted in contracted, relapsed clubfoot tissue. This was accompanied by a significant increase in the levels of the vascular endothelial growth factor, vascular endothelial growth factor receptor 2, β catenin and active β catenin. Vascular endothelial growth factor, vascular endothelial growth factor receptor 2, and CD31 overexpression was also seen with mRNA analysis. CONCLUSIONS: Increased microvessel and arteriole density in the contracted side of the relapsed clubfoot was noted. These processes are mediated by specific proangiogenic proteins that are overexpressed in the contracted tissue. These findings contribute to the etiology and the development of relapses in the treatment of clubfoot. LEVEL OF EVIDENCE: Level II-analytical and prospective.
Keywords: patologická angiogeneze; beta-katenin; Recurrence; Female; Casts, Surgical; předškolní dítě; výsledek terapie; Arterioles; ženské pohlaví; vaskulární endoteliální růstový faktor A; lidé; pes equinovarus; recidiva; sádrové obvazy; Vascular Endothelial Growth Factor A; Treatment Outcome; Clubfoot; prospektivní studie; Male; Prospective Studies; Child, Preschool; receptor 2 pro vaskulární endoteliální růstový faktor; arterioly; Neovascularization, Pathologic; Vascular Endothelial Growth Factor Receptor-2; mužské pohlaví; beta Catenin; Humans